PKM Katekese tentang Cinta dalam Perkawinan Kristiani bagi Keluarga Katolik di Paroki St. Petrus Kloangpopot - Aurelius Fredimento; Gregorius Sebo Bito; Ferdinandus Etuasius Dole (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2023)
All Catholic husband and wife couples must have a strong desire for a happy and prosperous married life in the future. Likewise with the Catholic husband and wife at St. Parish. Petrus Kloangpopot must also have a dream so that in the future their married life will always be happy and prosperous. They will continue to make various concrete efforts so that all these dreams can come true. Falling and getting up, crying and disappointment in pursuing such a dream they must have continued to experience. Tired and hopeless, of course, have become an integral part of the dynamics of their marriage journey. It must be accepted that sometimes the struggle to achieve a happy and prosperous Christian married life always goes wrong. This is actually caused by the weak internalization of love in marriage. Understanding of husband and wife Catholic Parish St. Petrus Kloangpopot about love as the foundation of their marriage is still far from expectations. Based on these considerations, the Parish Church of St. Petrus Kloangpopot together with all of his pastoral apparatus, feel responsible for reinstilling the understanding of love in marriage through various programs of Family Pastoral Work. One of its work programs is to hold catechism activities for husband and wife at St. Petrus Kloangpopot. This activity aims to reopen their point of awareness that love will always be the basis for the creation of a happy and prosperous Christian family life. This catechism activity was held on June 4 2023 using the Living-Scripture-Notes method with 25 married couples participating.